PENGARUH PENDIDIKAN KESEHATAN TERHADAP GAMBARAN DIRI SISWI SEKOLAH DASAR DALAM MENGHADAPI MENARCHE DI SD KECAMATAN JETIS YOGYAKARTA - , NILA RIZAYANTI; , Wenny Artanty Nisman, S.Kep., Ns., M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Teenage period is the period of transition from childhood to adolescence characterized by the presence of puberty. Girls face puberty early, as indicated from the incidence of menarche. Average age of menarche tends to decline over years. Menarche at early age can cause anxiety. Unless there is psychological preparedness and adequate information, menarche can become a traumatic experience. Objective: To identify effect of health education to body image of female elementary school students facing menarche at elementary schools of Sub District of Jetis, Yogyakarta. Method: The study was a pre experiment with one group pretest posttest design without control undertaken at 15 elementary schools all over Sub District of Jetis Yogyakarta in August - October 2012. Samples consisted of 283 female students taken through total sampling technique. Research instrument was questionnaire of body image. Data analysis used Wilcoxon and Paired t test. Result: The result of the study showed score of mean of body image during pretest was 82.7 and posttest 83.7. The result of Wilcoxon showed there was no significant difference in body image before and after health education with the mix between lecture and audiovisual media (p>0.05). Body image consisted of four components, i.e. perception, affective, cognitive, and behavior. The result of score of mean during pre test and post test showed increase in components of affective, cognitive, and behavior. Cognitive component was one that showed significant change. Conclusion: There was no effect of health education to body image of female elementary school students facing menarche at elementary schools of Sub District of Jetis, Yogyakarta.